Restaurer la continuité écologique des cours d’eau : que sait-on et comment passer collectivement à l’action ? - Maria Alp; Fanny Arnaud; Carole Barthélémy; Ivan Bernez; Anne Clemens; Marylise Cottet; Simon Dufour; Marie-Anne Germaine; Christelle Gramaglia; Stéphane Grivel; Céline Le Pichon; Laurent Lespez; et al. (VertigO)
The result of work of an interdisciplinary group of researchers of the French Workshop Zone Network (Réseau des Zones Ateliers, CNRS), this article focuses on the implementation of restoration projects aiming to restore ecological connectivity of rivers. These projects are at the center of an important controversy taking place in the French public space since several years. Thus certain actors put into question the pertinence of the public policy aiming at removal of hydraulic structures contributing to connectivity interruption. Here, we first synthesize the currently known effects of the connectivity interruption in its longitudinal, lateral and vertical dimensions on a row of biophysical and socio-economic processes. Spotlighting the complexity of processes linked to river connectivity, the variablity of territorial contexts and the associated uncertainties, our analysis reveals the necessity of inscribing restoration projects within a larger project of water ressource management conducted at the scale of a territory and rooted in a participatory decision process. The decision to restore or not restore connectivity cannot be based exclusively on science and technical expertise. With this in mind, we propose an action strategy to address challenges related to river connectivity restoration. We identify ten critical points to take into account for implementing restoration projects that would be both supported by different stakeholders, and efficient in regard to their defined objectives.